Junior High School Teachers' Strategies in utilizing E-learning-based Audio-Visual Media in Science Learning at School - Mochamad Solihin; Dwi Hariyanti (Indonesian Journal of Innovative Teaching and Learning, 2025)
Background: The rapid shift to digital learning during the COVID-19 pandemic has compelled educators to adopt innovative teaching strategies, particularly through the integration of e-learning-based media. One such approach involves the use of audio-visual media to enhance the effectiveness of science education. Objective: This study aims to determine the teacher's strategy in utilizing e-learning-based audio-visual media at SMP Negeri 12 Cimahi in learning Natural Sciences. Method: This study used a qualitative approach with a field research method. Data collection was done through observation, interview, and documentation. Data validity was tested through credibility, transferability, dependability, and confirmability tests. The data obtained were analyzed through data processing, classification, interpretation, and conclusion drawing. Results: The use of audio-visual media during the COVID-19 pandemic at SMP Negeri 12 Cimahi has been running well in online and offline learning. Conclusion: E-learning-based audio-visual media has proven effective in increasing student engagement, clarifying complex concepts, and increasing learning motivation. Contribution: This study contributes insight into the importance of using e-learning-based audio-visual media in improving the effectiveness of science learning, especially in emergencies such as a pandemic.